Exome sequencing in fetuses with short long bones detected by ultrasonography: A retrospective cohort study - Huang, Yanlin; Liu, Chang; Ding, Hongke; Wang, Yunan; Yu, Lihua; Guo, Fangfang; Li, Fake; Shi, Xiaomei; Zhang, Yan; Yin, Aihua (Frontiers in Genetics, 2023)
Background: Prenatal diagnosis of fetal short long bones (SLBs) was reported to be associated with skeletal dysplasias, chromosomal abnormalities, and genetic syndromes. This study aims to identify the genetic causes for fetal SLBs, and retrospectively evaluate the additional diagnostic yield of exome sequencing (ES) for SLBs following the use of conventional genetic testing. Methods: A cohort of ninety-four fetuses with sonographically identified SLBs was analyzed by trio-ES between January 2016 and June 2021. Fetuses with abnormal results of karyotype or chromosomal microarray analysis were excluded. Variants were interpreted based on ACMG/AMP guidelines. All diagnostic de novo variants were validated by Sanger sequencing. Results: Of the 94 fetuses, 38 (40.4%) were found to carry causal genetic variants (pathogenic or likely pathogenic) in sixteen genes with 38 variants. Five fetuses (5.3%) had variant(s) of uncertain significance. Thirty-five cases (37.2%) were diagnosed as genetic skeletal dysplasias including 14 different diseases that were classified into 10 groups according to the Nosology and Classification of Genetic Skeletal Disorders. The most common disease in the cohort was achondroplasia (28.9%), followed by osteogenesis imperfecta (18.4%), thanatophoric dysplasia (10.5%), chondrogenesis (7.9%), and 3-M syndrome (5.3%). The diagnostic yield in fetuses with isolated SLBs was lower than the fetuses with non-isolated SLBs, but not reached statistical significance (27.3% vs 44.4%; P=0.151). Whereas, the rate in the fetuses with other skeletal abnormalities was significantly higher than those with non-skeletal abnormalities (59.4% vs 32.5%, P=0.023), and the diagnostic rate was significantly higher in femur length (FL) below -4SDs group compared with FL 2-4SDs below GA group (72.5% vs 16.7%; P<0.001). A long-term follow-up showed that outcomes for fetuses with FL 2-4SDs below GA were significantly better than those with FL below -4SDs. Additionally, fourteen (36.8%) novel SLBs-related variants were identified in the present study. Conclusions: The findings suggest that in fetuses with SLBs routine genetic tests failed to determine the underlying causes, ES could add clinically relevant information that could assist the clinical management of pregnancies. Novel pathogenic variants identified may broaden the mutation spectrum for the disorders and contributes to clinical consultation and subsequent pregnancy examination.